Reclaiming the Sane Society
XXIV, 224 p.
Keywords: Erich Fromm’s body of work, written more than 50 years ago, was prophetic of the contemporary moment: Increasingly, global society is threatened by the many-headed monster of corporate greed, neo-liberalism, nihilism, extreme fundamentalist beliefs, and their resulting effects on the natural world and the lived lives of people. Fromm clearly warned us of the peril of the misuse of technology and the destructive nature of man’s perverse desire to possess, control and/or destroy. Through his theories of having vs. being, the importance of hope as active resistance, and his notion of freedom as the capacity to love self, and others, Fromm encouraged his readers to cultivate biophilic ways of being in the world that will counter and heal the impending necrophilic plunder of man’s hubris. This multi-authored volume sheds new light on Fromm’s forgotten role in the formation of contemporary thought through an engaging variety of reflexive and historical narratives from fields of sociology, clinical psychology, political science, critical theory of religion and education. Key concepts from his body of work are interpreted and expressed in ways that offer hopeful and humane alternatives to the present global conditions of despair, greed and depersonalization.